Ekstraksi Komponen Fenolat dari Liang Teh Pontianak Perisa Jahe Secara Partisi - Nada, Geri; Dewi, Yohana Sutiknyawati Kusuma; Fadly, Dzul (Jurnal Teknologi dan Industri Pertanian Indonesia, 2024)
Liang Teh Pontianak (LTP) is one of the beverages traditionally consumed as a functional drink. Liang teh is an herbal drink composed of various plant ingredients including secang stem bark, muje leaves, nanas kerang leaves, oregano leaves, pandan leaves, and lidah buaya mid rib, which known for their medicinal and health benefits. The aim of this study was to identify the phenolic components of ginger-flavored LTP through partition extraction. The plant materials were processed into powder and formulated to a total of 21 grams, consisting of 10 g of muje leaves, 1 g of oregano leaves, 1 g of aloe vera mid rib, 2.5 g of nanas kerang leaves, 4.5 g of secang stem bark, 1 g of pandan leaves, and 1 g of ginger as the tea flavor. The mixture of Liang teh powder then partitioned using various solvents in order of increasing polarity, namely n-hexane, ethyl acetate, ethanol, methanol, 70:30 methanol-water (v/v) mixture, and water. The research results showed that extracts from all solvent types contained alkaloids, phenols, flavonoids, and tannins. The highest yield was obtained from the ethanol extract (6.100.35) %, while the highest antioxidant activity was found in the methanol extract (84.431.38) %.